ANALISIS KECENDERUNGAN PERILAKU CYBERSLACKING TERHADAP RESILIENSI AKADEMIK MAHASISWA - PADILLAH . (LP2MTBM MAKARIOZ, 2021)
Organization is a consciously coordinated social unity, which allows members to achieve goals that cannot be achievedthrough individual actions separately. Kast & Rosenzweig (in Munandar, 2001) says that an organized whole unit, consistingof two or more interdependent, component or subsystem, separated from the suprasystem as its environment bydiscoverable boundaries. Learners can learn anytime and anywhere unlimited by distance, space, and time. This is one ofthe positive impacts of current technological advances in the field of education. In addition to the positive impact resultingfrom this technology, these technological advances also have a negative impact, one of which is cyberslacking.Cyberslacking is defined as conscious behavior engaged by an employee to access things that are not related to his or herjob by using the company's internet access. Cyberslacking is the behavior of students who use the internet during lessonhours for personal gain and activities unrelated to the network. Other words commonly mentioned in inappropriate orunrelated internet use include junk computing, cyberslacking, or cyberloafing.